2021
DOI: 10.1016/j.eats.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet-Rich Fibrin Matrix–Augmented Repair for Parameniscal Cysts: Surgical Technique

Abstract: Parameniscal cysts are defined as an internal disorder of the knee joint. It is known that parameniscal cysts are associated with horizontal meniscal tears that could lead to the collection of synovial fluid within the cyst. Despite the treatment of meniscal tears, cyst recurrence is still an issue that needs to be addressed. In this regard, there has been an increasing interest in the use of biologic agents to enhance the vascularity and healing of the meniscus. Preliminary results for biologic therapeutic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Because cysts are frequently located in the vascular zone and the parameniscal region in cases of horizontal tears, efforts to perform minimized meniscectomy are required to avoid sequalae such as degenerative arthritis. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Because cysts are frequently located in the vascular zone and the parameniscal region in cases of horizontal tears, efforts to perform minimized meniscectomy are required to avoid sequalae such as degenerative arthritis. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…The cyst is evacuated. The autologous platelet-rich fibrin matrix membrane is located in the outer layer of the lateral meniscus and then sutured side-to-side to the adjacent capsule by adsorbable suture [ 15 ] (Fig. 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…84 In 2021, Screpis and colleagues utilized PRF to repair parameniscal cysts, describing their surgical technique. 85 In 2022, Narayanaswamy and Sha described a reproducible and simple way to harvest PRF and create and use a PRF clot, along with detailed instructions on how to integrate the clot with a meniscal repair arthroscopically. 86 Therefore, although studies remain in their infancy, various research groups have demonstrated promising results utilizing i-PRF for joint injections (Figure 15, Figure S1: QR Code 10 ).…”
Section: Clinical Use Of I-prf For Cartilage Regeneration and Osteoar...mentioning
confidence: 99%
“…created a method to utilize PRF for meniscus tear repair 84 . In 2021, Screpis and colleagues utilized PRF to repair parameniscal cysts, describing their surgical technique 85 . In 2022, Narayanaswamy and Sha described a reproducible and simple way to harvest PRF and create and use a PRF clot, along with detailed instructions on how to integrate the clot with a meniscal repair arthroscopically 86 .…”
Section: Medical Applicationsmentioning
confidence: 99%